Coping in the Aftermath of Youth's Suicidal Behaviors: A Comparison of Black Mothers and White Mothers. Issue 1 (25th August 2020) - Doyle, Otima; Weller, Bridget E.; Goldston, David B.; Breland‐Noble, Alfiee M.; Estroff, Sue E.; Daniel, Stephanie S.; Curry, John F.; Wells, Karen C.
Abstract : Objective: To better understand Black mothers' and White mothers' qualitative reactions to their adolescents' hospitalizations due to suicide attempts. Background: Caregivers of youth with suicidal behaviors play a vital role in youth's subsequent treatment and recovery. Yet little attention has been paid to how they are affected by youth's psychiatric hospitalizations or how their reactions may be influenced by race. Method: Twenty Black mothers ( M age  = 42.50; SD  = 8.48) and 20 White mothers ( M age  = 44.85; SD  = 6.86) were randomly selected from data originally collected for a larger longitudinal, mixed method, multisite study. Data analysis was informed by grounded theory methodology. Results: Four themes emerged from the data: mothers' emotional distress; mothers' coping, needs, and supports; mothers' perceived need for increased monitoring; and improved mother–child relationships. Conclusions: Black mothers and White mothers largely had similar reactions to youth's hospitalizations; however, nuanced differences also were noted regarding how they described their experiences and what they emphasized. Implications: During discharge planning, mothers need additional support (beyond referrals) in their roles as caregivers and for their own coping. Additional clinical and research implications are discussed.